Suplemen Toleransi pada Materi Bahan Ajar Pendidikan Agama Islam dan Budi Pekerti untuk Sekolah Menengah Pertama - Muhtarom, Dede Ahmad; Siswanto, Nopri Dwi; Amri, Ulil; Alim, Akhmad (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The Tolerance Supplement to the Islamic Religious Education and Ethics Teaching Materials for Junior High School is an educational initiative that aims to enrich the educational curriculum with the values of tolerance in Islam. Recognizing the importance of tolerance in Islamic religion and social life, this supplement presents modules designed to educate students on the importance of respecting differences, addressing conflicts wisely, and strengthening harmonious relationships in a multicultural society. Through diverse approaches such as discussions, case studies, collaborative projects, and the use of technology, students are invited to engage in interesting and relevant learning, thus enabling them to better internalize the values of tolerance. This research uses a qualitative approach by applying participatory observation and in-depth interview methods. Observations were made to observe the learning process involving the use of tolerance supplements in Islamic Religious Education and Ethics teaching materials in several junior high schools that have adopted these supplements. This supplement provides opportunities for students to explore the concept of tolerance through various learning modules, practical activities, and approaches that actively involve students in the learning process. Nevertheless, it is necessary to regularly evaluate the teaching process and students' understanding to improve the effectiveness of this supplement. Overall, the Tolerance Supplement to the Islamic Religious Education and Ethics Teaching Materials for Junior High School is an important and relevant initiative in shaping students' attitudes and characters that are inclusive, tolerant, and ready to live in a diverse society.